2014
DOI: 10.1016/j.jfoodeng.2013.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Microfiltration of passion fruit juice using hollow fibre membranes and evaluation of fouling mechanisms

Abstract: a b s t r a c tThis work evaluated the microfiltration process for the clarification of passion fruit juice. Moreover, the influence of some pretreatments (centrifugation, enzymatic liquefaction and chitosan coagulation) before passion fruit juice microfiltration was analyzed. Enzymatic treatment reduced the juice viscosity, and centrifugation step was important for colour and turbidity reductions. Chitosan addition was the most promising pretreatment, since it provides the highest reductions of colour and tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 28 publications
4
27
0
6
Order By: Relevance
“…There was a great reduction in the turbidity rate after the microfiltration process due to the removal of macromolecules from the raw pulp. Domingues et al (2014) also observed a decrease in turbidity after microfiltration of passion fruit juice. Decrease in turbidity enhances juice commercialization due to lower decantation of suspended solids.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…There was a great reduction in the turbidity rate after the microfiltration process due to the removal of macromolecules from the raw pulp. Domingues et al (2014) also observed a decrease in turbidity after microfiltration of passion fruit juice. Decrease in turbidity enhances juice commercialization due to lower decantation of suspended solids.…”
Section: Methodsmentioning
confidence: 73%
“…Further, the microfiltration process eliminates microorganisms and compounds which cause juice turbidity (Coutinho et al, 2009;Girard & Fukumoto, 2000). Membrane technology has been largely applied for the processing of some juices, such as apple, tomato, pineapple and passion fruit juices (Domingues, Ramos, Cardoso, & Reis, 2014;Girard & Fukumoto, 2000). Machado, Haneda, Trevisan, and Fontes (2012) analyzed the influence of the microfiltration process on the antioxidant capacity of the obtained permeate of açaí juice and observed that this parameter was reduced by 36 and 27% for açaí juices with and without enzymatic pretreatment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fouling mechanism most probably occurred due to cake formation, since the molecule size plays a key role in molecule accumulation on the membrane surface (Domingues et al, 2014) The high pressures used in this experiment may have also contributed to the formation of a fouling layer on the membrane surface. According to Mirsaeedghazi et al (2009) and Razi et al (2012), fouling correlates positively with the increase in transmembrane pressure and temperature by increasing the macromolecule diffusion coefficient and favoring penetration and deposition in the membrane pores (Wang et al, 2012).…”
Section: Manufacturing Processmentioning
confidence: 96%
“…Osmotic evaporation (OE) is a variant of membrane distillation (MD), whose process uses hydrophobic membranes, wherein the pores are filled with the gas phase of the fluid to concentrate, thus preventing water penetration so that only volatile components are transported through the membrane [5]. The vapor partial pressure difference between liquids separated by the membrane is the process' driving force, and its value depends on the temperature and composition of layers adjacent to the membrane surface, whose effect may generate this partial pressure gradient [6,7].…”
Section: Introductionmentioning
confidence: 99%